2021
DOI: 10.1080/19768354.2021.2006310
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the differential genomic variants using cross-population phenotype-associated variant (XP-PAV) of the Landrace and Yorkshire pigs in Korea

Abstract: Although there have been many genome-wide association studies (GWAS) and selective sweep analyses to understand pig genomic regions related to growth performance, these methods considered only the gene effect and selection signal, respectively. In this study, we suggest the cross-population phenotype associated variant (XP-PAV) analysis as a novel method to determine the genomic variants with different effects between the two populations. XP-PAV analysis could reveal the differential genetic variants between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a dimension reduction method, principal component analysis (PCA) combines multiple features into lower-dimensional features, that can explain most of the variance in a large dataset (Lee et al 2021 ). PCA was conducted using genome-wide complex trait analysis (GCTA) to obtain eigenvalues and eigenvectors (Yang et al 2011 ) and to assess the explanatory power of each breed-specific SNPs, which revealed that breed-specific SNPs can distinguish them from other breeds.…”
Section: Methodsmentioning
confidence: 99%
“…As a dimension reduction method, principal component analysis (PCA) combines multiple features into lower-dimensional features, that can explain most of the variance in a large dataset (Lee et al 2021 ). PCA was conducted using genome-wide complex trait analysis (GCTA) to obtain eigenvalues and eigenvectors (Yang et al 2011 ) and to assess the explanatory power of each breed-specific SNPs, which revealed that breed-specific SNPs can distinguish them from other breeds.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) aim to detect variants of genomic loci associated with complex traits in the population, and common single nucleotide polymorphisms (SNPs) are the main source of these variants. SNPs are used to describe genetic variability and identify candidate genes, and GWAS examine significant SNPs (Lee et al 2021 ; Lee et al 2022 ). Attempts to use linkage analysis for mapping genomic loci that affect complex traits are ubiquitous.…”
Section: Introductionmentioning
confidence: 99%